Oxygen Consumption and Ammonia Excretion Rates of the Sea Cucumber Holothuria spinifera, (Theel, 1886) in Relation to Reproductive Stages - S, ASHA P (Fishery Technology, 2023)
The knowledge on oxygen consumption and ammonium excretion rates of aquaculture species are important aspects useful in their captive management. It will help in understanding their energetic role and material recycling in an ecosystem. A study was conducted to assess the rates of oxygen consumption (OCR) and ammonia excretion (AER) in Holothuria spinifera with respect to reproductive stages following standard techniques. The OCR was comparatively higher for the indeterminate animals and the mean OCR was maximum of 0.025 ± 0.021 ml O2 hr-1g-1 dry wt in the indeterminate stage-two. Whereas the AER was comparatively higher in the spent stages of both the sexes and the mean value was highest of 20.03 ± 0.15 µg atom N hr-1 g-1 dry wt for the spent male. In this study the smallest individual exhibited the highest rate of oxygen consumption and ammonia excretion. The body size and metabolic rate are important in assessing the organism impact on the environment.